Performance Evaluation of Three PID Controller Tuning Algorithm on a Process Plant - Oladimeji Ibrahim; Sulyman A. Y. Amuda; Olatunji O. Mohammed; Ganiyu A. Kareem (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Accurate tuning of controller in industrial process operation is prerequisite to system smooth operation which directly reduce process variability, improved efficiency, reduced energy costs, and increased production rates. Performance evaluation of a model based PID controller tuning algorithm on a chemical process plant is presented in this paper. The control action of three different PID controller tuning algorithms namely; Hagglund-Astrom, Cohen and Coon, and Ziegler-Nichols on the process plant was examined in a closed loop control configuration under normal operating condition and in the face of disturbance. LabVIEW software was used to model a chemical process plant from open loop control test data. The time domain response analysis of the controllers shows that each tuning algorithm exhibit different time response. Ziegler-Nichols algorithm shows the best performance with fastest rise time, settling time and was able to restore the system back to normal operating condition in a short time when subjected to disturbance compare to Cohen & Coon controller and Hagglund-Astrom algorithm settings.